The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1186/s10195-023-00694-7
|View full text |Cite
|
Sign up to set email alerts
|

Suprapatellar vs infrapatellar approaches for intramedullary nailing of distal tibial fractures: a systematic review and meta-analysis

Abstract: Background This review was conducted to compare the efficacy of suprapatellar (SP) and infrapatellar (IP) approaches for treating distal tibial fractures with intramedullary nailing. Method This systematic review included studies comparing the outcomes of patients receiving nailing for distal tibial fractures using the SP and IP approaches. We searched the Cochrane CENTRAL, MEDLINE and Embase databases for relevant studies till 18th Sep. 2022. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Since the implementation of SP IMN into the treatment protocol of tibial fractures at our hospital, peri- or postoperative fasciotomies have not been required. To our knowledge, some benefits of using SP approach have been reported, but no previous studies are concerning ACS and the need for fasciotomies in relation to the nailing technique chosen [ 19 , 25 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the implementation of SP IMN into the treatment protocol of tibial fractures at our hospital, peri- or postoperative fasciotomies have not been required. To our knowledge, some benefits of using SP approach have been reported, but no previous studies are concerning ACS and the need for fasciotomies in relation to the nailing technique chosen [ 19 , 25 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, fasciotomies might not have been considered as a complication of a surgical method but rather a treatment of compartment syndrome resulting from the fracture itself. To date, only a few studies have reported the rates of fasciotomies in association to the treatment of tibial fractures using an intramedullary nail [ 25 , 32 34 ]. ACS and fasciotomies after tibial fracture are associated with a higher risk for complications, slower fracture healing, and poor functional outcomes [ 3 , 7 , 10 , 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations